The Impact of Antidiabetic Agents on Sarcopenia in Type 2 Diabetes: A Literature Review - Chen-Ning Wu; Kai-Jen Tien (Journal of Diabetes Research)
Sarcopenia is a geriatric syndrome characterized by decline of skeletal muscle mass and function. Contributing factors include nutritional, genetic, inflammatory, and endocrinal factors. The reported prevalence of sarcopenia in type 2 diabetes mellitus is high, especially in patients with poor glycemic control. Additionally, antidiabetic agents may alter the balance between protein synthesis and degradation through various mechanisms of skeletal muscle mass regulation. This study reviewed the literature on the pathogenesis of sarcopenia in diabetes mellitus and the current understanding of whether antidiabetic agents contribute positively or negatively to sarcopenia and muscle wasting.